2003
DOI: 10.1614/p2002-159
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of extreme genetic recombination in weedy Amaranthus hybrids

Abstract: Interspecific hybridization of Palmer amaranth and common waterhemp produce hybrids with unique DNA fragments not found in either parent. The objective of this research was to investigate the mechanisms involved in the formation of the polymorphic fragments. Six novel fragments were cloned and sequenced. Five of the six were significantly similar to plant transposons, the sixth was similar to squamosa promoter–binding proteins from other plant species. Southern blot analysis using one of the novel fragments as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…rudis and A. palmeri was intermediate between the parents. Other morphological characters may not be intermediate between the two parents (Steinau et al 2003), as has also been reported for hybrids between monoecious species of the section Amaranthus (Costea and Tardif 2003b;Costea et al 2004). The presence of morphological characteristics absent in parent species may be explained by the formation of polymorphic DNA fragments resembling transposon-like elements (Wetzel et al 1999b;Steinau et al 2003).…”
Section: Hybridsmentioning
confidence: 69%
See 3 more Smart Citations
“…rudis and A. palmeri was intermediate between the parents. Other morphological characters may not be intermediate between the two parents (Steinau et al 2003), as has also been reported for hybrids between monoecious species of the section Amaranthus (Costea and Tardif 2003b;Costea et al 2004). The presence of morphological characteristics absent in parent species may be explained by the formation of polymorphic DNA fragments resembling transposon-like elements (Wetzel et al 1999b;Steinau et al 2003).…”
Section: Hybridsmentioning
confidence: 69%
“…Other morphological characters may not be intermediate between the two parents (Steinau et al 2003), as has also been reported for hybrids between monoecious species of the section Amaranthus (Costea and Tardif 2003b;Costea et al 2004). The presence of morphological characteristics absent in parent species may be explained by the formation of polymorphic DNA fragments resembling transposon-like elements (Wetzel et al 1999b;Steinau et al 2003). First generation hybrids between dioecious and monoecious, or between monoecious Amaranthus species, have reduced fertility, low vigor and slow growth, distorted leaves, abnormally shaped inflorescences, and numerous, densely packed bracteoles.…”
Section: Hybridsmentioning
confidence: 69%
See 2 more Smart Citations
“…Hybridization among different species has been widely reported within the genus Amaranthus (Sauer 1950;Trucco et al 2005). Wetzel et al (1999) reported transfer of ALS resistance via hybridization and backcrossing between Palmer amaranth and common waterhemp, although Franssen et al (2001), Steinau et al (2003), and Trucco et al (2007) found very low levels of hybridization with most hybrid progeny from this cross either nonviable or sterile. Gaines et al (2012) also reported low levels (, 0.2%) of interspecific hybridization between Palmer amaranth and common waterhemp, with even lower levels (, 0.01%) of hybrid formation between Palmer amaranth and smooth pigweed (A. hybridus L.).…”
mentioning
confidence: 99%